The clinical efficacy of monolayer suture combined with hem-o-lok clip in partial nephrectomy among patient with renal cell carcinoma: a quasi-experimental study - Guochang Zheng; Jinming Li; Qiang Zhao; Hongfeng Nie; Liyan Zhao; Jing Zhang (World Journal of Surgical Oncology)
Abstract Objective To explore the clinical efficacy of monolayer suture combined with a hem-o-lok clip during partial nephrectomy among patients with renal cell carcinoma (RCC). Methods Eighty patients with RCC underwent laparoscopic partial nephrectomy from January to October 2021. They were assigned into a control group and an intervention group, each with 40 cases using random number table. The control group received double-layer sutures on the wound, while the intervention group had single-layer sutures with a hem-o-lok clip for hemostasis. The study compared operative indexes and postoperative recovery of the two groups. Results Intraoperative bleeding and warm ischemia time in the intervention group were significantly shorter than that in the control group. There were no significant differences in operation time, drainage volume on the first day after operation, and hospital stay between the two groups. Before operation, there were no significant differences in serum creatinine and blood urea nitrogen between the two groups. However, 24 h post-operation, both groups experienced a significant increase in these levels, with the intervention group showing lower levels than the control group. Changes in glomerular filtration rate were significantly lower in the intervention group than the control group. Complication rates were similar, with 7.5% in the research group and 10.0% in the control group. Conclusion Monolayer suture combined with a hem-o-lok clip can shorten the time of warm ischemia, reduce intraoperative bleeding and the loss of normal renal parenchyma in patients undergoing laparoscopic partial nephrectomy. More studies with larger sample size are needed to confirm the results.